2020
DOI: 10.1007/978-3-030-59728-3_14
|View full text |Cite
|
Sign up to set email alerts
|

Infant Cognitive Scores Prediction with Multi-stream Attention-Based Temporal Path Signature Features

Abstract: There is stunning rapid development of human brains in the first year of life. Some studies have revealed the tight connection between cognition skills and cortical morphology in this period. Nonetheless, it is still a great challenge to predict cognitive scores using brain morphological features, given issues like small sample size and missing data in longitudinal studies. In this work, for the first time, we introduce the path signature method to explore hidden analytical and geometric properties of longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Considering the average performance of all tasks, our method reaches a state-of-the-art RMSE 0.1631. It is noteworthy that BrainPSNet [24] introduces the path signature in equation ( 2) to describe the development pattern of brain regions, but it is poor-performed for neglecting the graph structure among brain regions and the benefits may brought by the learnable matrices in equation (3).…”
Section: Ablation Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the average performance of all tasks, our method reaches a state-of-the-art RMSE 0.1631. It is noteworthy that BrainPSNet [24] introduces the path signature in equation ( 2) to describe the development pattern of brain regions, but it is poor-performed for neglecting the graph structure among brain regions and the benefits may brought by the learnable matrices in equation (3).…”
Section: Ablation Studymentioning
confidence: 99%
“…Learning a set of compact representations, which effectively capture the spatial and temporal cortical developmental patterns, is one of the most important techniques to deal with the small sample size problem. However, existing methods usually simply flatten brain morphological feature vectors at every time point into a vector [1,23,24], which obviously neglect the potential connectivity among brain regions. It has been revealed that the massive brain region connections form elegant topologies, such as small-worldness and modular organization, which can be probed using the graph theoretical modeling method [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, path signature features, extracted by a differentiable temporal path signature (TPS) layer, can effectively describe dynamic properties of the cortical growth trajectory. With the help of an attention mechanism to automatically weight brain regions at different time points, encouraging results can be obtained [22].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, based on our previous work [22], we stack the light-weight TPS layers to obtain a global receptive field and aggregate features from all existing visits. Compared to [12], [13], their mapping function is a single-layer nonlinear function, since it is risky to apply its complicated substitutes such as RNNs with the SSS problem, while the hierarchical structure of dynamic patterns may be overlooked.…”
Section: Introductionmentioning
confidence: 99%